Block Hybrid k-Step Backward Differentiation Formulas for Large Stiff Systems. (20th October 2014) - Jator, S. N.; Agyingi, E.
Abstract : This paper presents a generalized high order block hybrid k -step backward differentiation formula (HBDF) for solving stiff systems, including large systems resulting from the semidiscretization parabolic partial differential equations (PDEs). A block scheme in which two off-grid points are specified by the zeros of the second degree Chebyshev polynomial of the first kind is examined for convergence, L and A stabilities. Numerical simulations that illustrate the accuracy of a Chebyshev based method are given for selected stiff systems and partial differential equations.